2020
DOI: 10.1371/journal.pone.0228673
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and multilocus genotyping of Giardia duodenalis in captive non-human primates from 12 zoos in China

Abstract: Giardia duodenalis is a common enteric protozoan that infects a range of hosts including humans and other mammals. Multilocus genotyping of G. duodenalis in captive non-human primates (NHPs) from zoos in China is limited. In this study, we evaluated 302 NHP fecal samples collected from 32 different NHP species. The primates were from 12 zoos distributed across eight provinces and two municipalities (Chongqing and Beijing) of China. The overall infection rate was 8.3% (25/302). The six G. duodenalis-positive zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Our genetic analyses revealed that eight out of 10 G. duodenalis infections were caused by the assemblage B of the parasite, and that all the genetic variants detected (sub-assemblages AI, AII, and BIV) were zoonotic (70). This predominance of assemblage B over assemblage A has been confirmed in other NHP populations from Belgium and the Netherlands (71), China (72)(73)(74), Croatia (65), Italy (66), the Republic of Congo (49), Slovakia (67), Sweden (75), and Thailand (52). However, it should be noted that this trend is far from general, and the opposite result (preponderance of assemblage A over assemblage B) has also been reported in captive NHP belonging to the genera Alouatta and Ateles in Brazil (76,77) and in different NHP collections from Spanish zoological gardens (13,68).…”
Section: Discussionsupporting
confidence: 73%
“…Our genetic analyses revealed that eight out of 10 G. duodenalis infections were caused by the assemblage B of the parasite, and that all the genetic variants detected (sub-assemblages AI, AII, and BIV) were zoonotic (70). This predominance of assemblage B over assemblage A has been confirmed in other NHP populations from Belgium and the Netherlands (71), China (72)(73)(74), Croatia (65), Italy (66), the Republic of Congo (49), Slovakia (67), Sweden (75), and Thailand (52). However, it should be noted that this trend is far from general, and the opposite result (preponderance of assemblage A over assemblage B) has also been reported in captive NHP belonging to the genera Alouatta and Ateles in Brazil (76,77) and in different NHP collections from Spanish zoological gardens (13,68).…”
Section: Discussionsupporting
confidence: 73%
“…In the current study, the infection rate of NHPs was 17.4% and close to the prevalence in Dalian zoo (16.7%) (Zhang et al ., 2020). It was higher than those reported in Qianling Park in Guiyang (8.5%) (Ye et al ., 2012), Sichuan and Guizhou provinces (7.7%) (Zhong et al ., 2017), Qinling Mountain (2.0%) (Du et al ., 2015) and two other additional comprehensive parasite infection studies in China (2.2 and 1.3%) (Ye et al ., 2012; Li et al ., 2017) Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Nested PCR protocols based on multiple-copy genes ( e.g. SSU rRNA ) have higher diagnostic sensitivities than those based on single-copy genes ( bg , gdh , and tpi ) [ 45 ]. Therefore, the SSU rRNA -positive samples not amplified at the other three loci may be due to the limited sensitivity of PCR in detecting the single-copy genes.…”
Section: Discussionmentioning
confidence: 99%